2022
DOI: 10.1002/1878-0261.13174
|View full text |Cite
|
Sign up to set email alerts
|

A pipeline for copy number profiling of single circulating tumour cells to assess intrapatient tumour heterogeneity

Abstract: Intrapatient tumour heterogeneity is likely a major determinant of clinical outcome in cancer patients. To assess heterogeneity in a minimally invasive manner, methods to perform single circulating tumour cell (CTC) genomics at high resolution are necessary. However, due to the rarity of CTCs, development of such methods is challenging. Here, we developed a modular single CTC analysis pipeline to assess intrapatient heterogeneity by copy number (CN) profiling. To optimize this pipeline, spike‐in experiments us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…At the genomic level, the highly multiplexed single nucleus sequencing (HM-SNS) has been demonstrated as a good tool to explore the heterogeneity of copy number profiling in the breast cancer [ 201 ], which has been applied to explain the chemoresistance revolution in TNBC [ 16 ]. Deger et al reported a modular pipeline constructed of five individually adjustable steps, including enrichment, isolation, whole-genome amplification, low pass sequencing, and bioinformatical analysis, to perform single CTCs genomics at a high resolution by copy number profiling [ 60 ]. Each step can be adjusted to use different methods according to specific research needs.…”
Section: Research Methods To Measure Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…At the genomic level, the highly multiplexed single nucleus sequencing (HM-SNS) has been demonstrated as a good tool to explore the heterogeneity of copy number profiling in the breast cancer [ 201 ], which has been applied to explain the chemoresistance revolution in TNBC [ 16 ]. Deger et al reported a modular pipeline constructed of five individually adjustable steps, including enrichment, isolation, whole-genome amplification, low pass sequencing, and bioinformatical analysis, to perform single CTCs genomics at a high resolution by copy number profiling [ 60 ]. Each step can be adjusted to use different methods according to specific research needs.…”
Section: Research Methods To Measure Heterogeneitymentioning
confidence: 99%
“…High throughput Loss of spatial information [ 16 , 201 ] Modular single CTC analysis pipeline Each step is adjustable. Preserving single-cell information Loss of spatial information [ 60 ] At the epigenomic level scATAC-seq Preserving single-cell information Loss of spatial information [ 10 ] scDNase-seq Preserving single-cell information Loss of spatial information [ 11 ] scNOMe–seq Preserving single-cell information Loss of spatial information [ 12 ] scChIP-seq Preserving single-cell information. High throughput Chip design is highly complex.…”
Section: Research Methods To Measure Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the VyCAP system (VyCAP BV, Enschede, The Netherlands) first distributes previously isolated CTCs onto a microwell chip, and following fluorescent image acquisition, the cells of interest are punched and collected one at a time through the chip . This system has been coupled with CellSearch for copy number profiling of single CTCs and as a pipeline has been validated in 2 mBRCA and 2 mPrCa patients . CellCelector (Sartorius AG, Göttingen, Germany) combines automated micromanipulation and microfluidic cell picking.…”
Section: State-of-the-art Approaches and Recent Advances In Ctc Isola...mentioning
confidence: 99%
“…41 This system has been coupled with CellSearch for copy number profiling of single CTCs and as a pipeline has been validated in 2 mBRCA and 2 mPrCa patients. 42 CellCelector (Sartorius AG, Goẗtingen, Germany) combines automated micromanipulation and microfluidic cell picking. Single CTCs isolated with CellCelector following their capture by Parsortix were successfully used for tumor engraftment in mice and single-cell transcriptomic analysis.…”
Section: Advances In Ctc Isolation and Sorting In Bulk And At The Sin...mentioning
confidence: 99%